Dampak Negatif Penggunaan Handphone Terhadap Pertumbuhan Dan Pendidikan Anak - Wahyuddin; Aidin (STKIP Al-Amin Dompu, 2025)
The use of mobile phones among children is increasing along with the development of technology. Although mobile phones have benefits in supporting learning, excessive and uncontrolled use can have negative impacts on children's physical, mental, and educational growth. This study aims to identify and analyze the negative impacts of mobile phone use on children, especially in terms of physical development (such as sleep disorders, body posture, and eye health) and in terms of education (decreased concentration in learning, game addiction, and decreased academic achievement). The method used is qualitative descriptive with observation, interviews and documentation in the field of children. The results of the study indicate that the use of mobile phones without parental supervision can hinder the learning process, reduce social interaction, and have a negative impact on children's physical health. Therefore, the active role of parents and teachers is needed in controlling and guiding children in using technology wisely.